Rozumienie potrzeb dzieci w standardzie kształcenia nauczycieli przedszkola i edukacji wczesnoszkolnej - Bartosz Atroszko (Problemy Wczesnej Edukacji)
The aim of the article is to present the results of a study on the understanding of children’s needs in the standard of education of preschool and early education teachers. The method used was a qualitative content analysis. Based on the results of the study, it was found that in the document analyzed, the understanding of children’s needs is very narrowly defined and largely limited to the issue of educational needs (including, in particular, special educational needs), pushing into the background or even omitting other mental needs of the youngest. In the context of the ongoing mental health crisis of young people, the lack of even a mention of the need for students to bond with other participants in school life, or their need for acceptance in a peer group, is particularly noteworthy.